Subcycle characterization of photoelectron emission with multicycle laser pulses - Ji, Qinying; Wang, Junping; Lu, Peifeng; Li, Hui; Gong, Xiaochun; Song, Qiying; Lin, Kang; Zhang, Wenbing; Ma, Junyang; Kling, Matthias Friedrich; Zeng, Heping; Wu, Jian; et al. (Physical Review A, 2017)
By partially overlapping two time-delayed orthogonally polarized multicycle laser pulses of the same carrier frequency, we construct an optical waveform whose polarization axis rotates slowly for consecutive optical cycles. This unique laser field tunnel-ionizes atoms and accelerates the freed electrons to different directions at different instants. Classical trajectory Monto Carlo simulations support the resulting angle-resolved photoelectron momentum distribution. Taking advantage of this optical field, we investigate characteristics of electrons triggered by different quarters of an optical cycle and explore the Coulomb focusing effect on electrons traveling along different trajectories. Our experiment using a polarization-skewed near-infrared laser pulse verifies the numerical simulations and demonstrates the feasibility of retrieving subcycle dynamics with multicycle laser pulses.
CRIS-Team Scopus Importer:2023-04-20